Faktor-Faktor Yang Mempengaruhi Rendahnya Pemakaian KB Implan Didesa Margamulya Wilayah Kerja Puskesmas Rambah Samo I - ,, ANDRIA (Jurnal Martenity and Neonatal, 2016)
Family planning is an attempt to space or plan the number and spacing of pregnancy by using contraceptives. Contraceptive implant is a contraceptive capsule shaped silastik contain hormones types of progestin (progestin synthetic) mounted underneath the skin method of contraceptive implant that is one of the methods available at the moment, seems less interested in the community, especially couples of childbearing age although the effectiveness of the contraceptive implant is very high namely its failure to 0.2-1 pregnancies per 100 women. The purpose of this research is knowing the factors that affect the low use of birth control implant Puskesmas Rambah Samo I. This type of research is descriptive research using cross sectional design with a sample of 71 people. The study was conducted in June, 2013 in the village of Margamulya. The results showed that the respondents' knowledge in the classification of pretty 49 people (69%), respondents aged 20-35 years are 40 (56.3%), cost of expensive implants majority of respondents said that 58 people (81.7%), respondents do not use implants for cosmetic reasons 35 people (49.3%), based on the side effects of 37 (52.4%), and based on the potential complications 48 people (67.6%). From the results of this study concluded that each of the factors affecting the low use of birth control implant Margamulya village Puskesmas Rambah Samo I.